Answer:
Step-by-step explanation:
<u><em>(1). 2 m / s²</em></u>
<u><em>(2). 0 m / s²</em></u> { Change from the previous section is - 2 m / s² }
<u><em>(3). - 8 m / s²</em></u> { Change from the previous section is - 8 m / s² }
<u><em>(4). - 1 m / s²</em></u> { Change from the previous section is + 7 m / s² }
<u><em>(5). 0 m / s²</em></u> { Change from the previous section is + 1 m / s² }
Answer:
Step-by-step explanation:
Given functions are,
f(x) = 2x - 3
g(x) = x³ - 2
h(x) = x² - 3x + 5
(10). f(4) = 2(4) - 3
= 5
g(-2) = (-2)³ - 2
= -8 - 2
= -10
f(4) + g(-2) = 5 -10 = -5
(11). g(3) = 3³ - 2 = 25
h(1) = 1² - 3(1) + 5
= 1 - 3 + 5
= 3
g(3) - h(1) = 25 - 3 = 22
(12). f(2) = 2(2) - 2 = 2
h(-3) = (-3)² - 3(-3) + 5
= -27 + 9 + 5
= -13
f(2).h(-3) = 2(-13) = -26
Answer:
y - 5 = 3 (x + 1)
Step-by-step explanation:
Start with the pertinent equation of a straight line: the point-slope form:
y-k = m(x-h), where (h,k) is the given point and m is the given slope.
Then y - 5 = 3(x-(-1) ), or y - 5 = 3 (x + 1).
Hey there!
All of the angles of a triangle add up to 180. We already have 65+79 which is 144. This means only need 36 more degrees to get to 180.
Therefore, your answer is A) 36°.
I hope this helps!
Longer side = sqrt2 * shorter side
= sqrt2 * 5/6 = 1.18 to nearest hundredth